2011
DOI: 10.1105/tpc.111.084715
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between the bHLH Transcription Factor FIT and ETHYLENE INSENSITIVE3/ETHYLENE INSENSITIVE3-LIKE1 Reveals Molecular Linkage between the Regulation of Iron Acquisition and Ethylene Signaling in Arabidopsis    

Abstract: Understanding the regulation of key genes involved in plant iron acquisition is of crucial importance for breeding of micronutrient-enriched crops. The basic helix-loop-helix protein FER-LIKE FE DEFICIENCY-INDUCED TRANSCRIPTION FACTOR (FIT), a central regulator of Fe acquisition in roots, is regulated by environmental cues and internal requirements for iron at the transcriptional and posttranscriptional levels. The plant stress hormone ethylene promotes iron acquisition, but the molecular basis for this remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
265
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 255 publications
(276 citation statements)
references
References 62 publications
6
265
0
1
Order By: Relevance
“…We tested if MED25 interacted with transcription factors involved in the regulation of iron homeostasis in Arabidopsis, i.e., FIT, PYE, bHLH038, bHLH039, EIN3 and EIL1 (Colangelo and Guerinot, 2004;Yuan et al, 2008;Long et al, 2010;Lingam et al, 2011). We found that MED25 interacted directly with EIN3 and EIL1, whereas YID1/ MED16 showed no interaction (Figure 5a).…”
Section: Med25 But Not Yid1/med16 Interacts With the Transcription Famentioning
confidence: 96%
See 4 more Smart Citations
“…We tested if MED25 interacted with transcription factors involved in the regulation of iron homeostasis in Arabidopsis, i.e., FIT, PYE, bHLH038, bHLH039, EIN3 and EIL1 (Colangelo and Guerinot, 2004;Yuan et al, 2008;Long et al, 2010;Lingam et al, 2011). We found that MED25 interacted directly with EIN3 and EIL1, whereas YID1/ MED16 showed no interaction (Figure 5a).…”
Section: Med25 But Not Yid1/med16 Interacts With the Transcription Famentioning
confidence: 96%
“…The two transcription factors in ethylene signaling, EIN3 and EIL1, directly interact with FIT, affecting the level of FIT protein (Colangelo and Guerinot, 2004;Lingam et al, 2011;Sivitz et al, 2011). It was propose that a small number of FIT proteins are activated during iron-deficient conditions, as large portions of the FIT proteins remain inactive.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations